Christian Nurses' Calling and Career Commitment in Indonesia: A Cross Sectional Study - Possumah, Keysia Crystania; Tampi, Gloria Natalia Yurikho; Mongdong, Agmitha Chellorina Olivia; Juniarta, Juniarta; Hasibuan, Shinta Yuliana (Nursing Current: Jurnal Keperawatan, 2023)
Calling is a strategy for discovering the purpose and significance of every individual, including the nurse. The awareness of a calling can motivate nurses to commit to a career. The greater nurses' awareness of their calling, the greater their devotion and sense of purpose in their work. The purpose of this study was to examine the relationship between calling and career commitment among Christian nurses in Indonesia. The study utilized a quantitative correlational method and cross-sectional approaches utilizing online survey technique. Accidental sampling was utilized, obtaining 96 Indonesian Christian nurses. The instruments were the Indonesian version of the Calling and Vocation Questionnaire (CVQ) (Alpha Cronbach = 0.873) and the Career Commitment Scale (CCS) questionnaire (Alpha Cronbach = 0.820). Data was analyzed using descriptive and bivariate analysis using Spearman rank correlation test. This study discovered a moderately positive correlation between a nurse's calling and career commitment (p = 0.001; r = 0.362). It is suggested that future research investigates other factors that may affect the nurse's career commitment. Understanding one's own calling as a nurse and acting on it is essential to increasing nurses' commitment to their profession.